1995
DOI: 10.1007/bf00028629
|View full text |Cite
|
Sign up to set email alerts
|

The labyrinth of nutrient cycles and buffers in wetlands: results based on research in the Camargue (southern France)

Abstract: Wetlands, especially in the Mediterranean area, are subject to severe eutrophication . T h i s m a y u p s e t t h e e q u i l i b r i u m b e t w e e n p h y t o p l a n k t o n p r o d u c t i o n i n u n d e s i r a b l e q u a n t i t i e s a n d a q u a n t i t a t i v e l y d e s i r a b l e m a c r o p h y t e p r o d u c t i o n . I n o r d e r t o m a n a g e t h i s e q u i l i b r i u m , a q u a n t i t a t i v e k n o w l e d g e o f n u t r i e n t i n p u t a n d f l u x e s i s e s s e n t i a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
9

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 44 publications
(34 reference statements)
1
52
0
9
Order By: Relevance
“…Human activities, such as agriculture and urban development, have been linked to increases in nutrient and sediment loading (Correll 1987;Turner and Rabalais 1991;Carpenter et al 1998) and can adversely affect water quality, productivity, and trophic structure (Ryding and Rast 1989;Rekolainen et al 1995;Rast and Thornton 1996) in receiving lakes, wetlands, estuaries, and coastal waters (Orth and Moore 1983;Officer et al 1984;Jordan et al 1991a, b;Frink 1991;Golterman 1995;Howarth et al 1996;Vukadin et al 1996;Carpenter et al 1998;Boesch et al 2001). Coastal watershed eutrophication has become a regional and global issue as larger proportions of the earth's human population settle in coastal areas (Valiela et al 1992;de Jonge et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Human activities, such as agriculture and urban development, have been linked to increases in nutrient and sediment loading (Correll 1987;Turner and Rabalais 1991;Carpenter et al 1998) and can adversely affect water quality, productivity, and trophic structure (Ryding and Rast 1989;Rekolainen et al 1995;Rast and Thornton 1996) in receiving lakes, wetlands, estuaries, and coastal waters (Orth and Moore 1983;Officer et al 1984;Jordan et al 1991a, b;Frink 1991;Golterman 1995;Howarth et al 1996;Vukadin et al 1996;Carpenter et al 1998;Boesch et al 2001). Coastal watershed eutrophication has become a regional and global issue as larger proportions of the earth's human population settle in coastal areas (Valiela et al 1992;de Jonge et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, these authors found that the uptake of phosphate due to microbial activity was approximately 30-40%. For a constant pH value in seawater and low phosphate concentrations, the adsorption process should dominate, whereas at higher P concentrations, apatite precipitation should become more important (Golterman 1995a), although it may be kinetically hindered (Yeoman et al 1988). The combination of precipitation and adsorption processes should decrease the possible fertilizing role of atmospheric P in crust-derived and/or Saharan rainwater in the surface marine layer.…”
mentioning
confidence: 99%
“…Sur ce sujet, Golterman (1992Golterman ( , 1994b) a publié deux revues pour les zones humides méditerranéennes.…”
Section: Resultsunclassified